2023
DOI: 10.1021/acs.iecr.3c02070
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Solubility in Fast Pyrolysis Bio-oil

Clarissa Baehr,
Ramazan Acar,
Chaima Hamrita
et al.

Abstract: Preheating and the use of additives, such as alcohols, are common strategies to treat fast pyrolysis bio-oil after production or before its intended use. Such strategies lower the viscosity of bio-oil and slow chemical reactions occurring in bio-oil during storage. Furthermore, they influence the physicalchemical properties, environmental performance, and cost of the final product. This work suggests the use of CO 2 as an alternative and environmental strategy. In contrast to other additives, CO 2 has the adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Pressurized CO 2 at 50 bar reduces the original viscosity of the wheat-straw-based FPBO used here by 70–80%, as does 5 wt % ethanol in FPBO. Further measurements have shown that a comparable viscosity reduction is achieved by the same mass fraction of solved CO 2 . Since the molar mass of CO 2 and ethanol is quite similar, this implies a similar mole fraction.…”
Section: Discussionmentioning
confidence: 73%
“…Pressurized CO 2 at 50 bar reduces the original viscosity of the wheat-straw-based FPBO used here by 70–80%, as does 5 wt % ethanol in FPBO. Further measurements have shown that a comparable viscosity reduction is achieved by the same mass fraction of solved CO 2 . Since the molar mass of CO 2 and ethanol is quite similar, this implies a similar mole fraction.…”
Section: Discussionmentioning
confidence: 73%
“…11,12 Bio-oil is seen as a potential feedstock for the production of biofuel. 13,14 Gases from pyrolysis could be combusted for providing heat required for pyrolysis. 15,16 As a waste in livestock production, pig manure production is relatively stable and has no seasonal fluctuations.…”
Section: Introductionmentioning
confidence: 99%